Effects of Metformin in High Concentrations on the Fertility of Female Sailfin Molly Poecilia latipinna - Abdul-Ameer M.F. Al-Hachamei; Hussein A. Saud; Sajed S. H. Alnoor (University of Thi-Qar Journal of agricultural research, 2024)
Metformin is a medicine that is used to treat type 2 diabetes and polycystic ovary syndrome (PCOS). This study investigated the effects of exposing the sailfin molly fish to sub-lethal concentrations of 0.008 mol.L-1 of metformin. The results showed that metformin caused disturbances in the endocrine glands, especially the pituitary hormones (GTHs). Metformin increased the expression of the Fshb and inhibited the Lhb genes in the pituitary gland, which led to higher levels of FSH and lower levels of LH hormones in the blood of fish. These hormonal changes led to irregularities in the ovarian development of female fish, such as an increase in the first stage of primary eggs and a delay in the final stage of embryo production.